2016
DOI: 10.1073/pnas.1611051113
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosomonas europaea cytochrome P460 is a direct link between nitrification and nitrous oxide emission

Abstract: Ammonia oxidizing bacteria (AOB) are major contributors to the emission of nitrous oxide (N 2 O). It has been proposed that N 2 O is produced by reduction of NO. Here, we report that the enzyme cytochrome (cyt) P460 from the AOB Nitrosomonas europaea converts hydroxylamine (NH 2 OH) quantitatively to N 2 O under anaerobic conditions. Previous literature reported that this enzyme oxidizes NH 2 OH to nitrite (NO − 2 ) under aerobic conditions. Although we observe NO − 2 formation under aerobic conditions, its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
217
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(226 citation statements)
references
References 49 publications
8
217
1
Order By: Relevance
“…Recent studies have suggested that the sole product of HAO oxidation of NH 2 OH is NO with a yield of three electrons, further suggesting that oxidation to NO 2 − is either abiotic or carried out by an unknown enzymatic step (37, 38). While this study suggests that abiotic oxidation of NO is a significant NO sink, a true yield of four electrons resulting from NO oxidation to NO 2 − by an unknown NO oxidase would result in increased biomass production by N. europaea .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that the sole product of HAO oxidation of NH 2 OH is NO with a yield of three electrons, further suggesting that oxidation to NO 2 − is either abiotic or carried out by an unknown enzymatic step (37, 38). While this study suggests that abiotic oxidation of NO is a significant NO sink, a true yield of four electrons resulting from NO oxidation to NO 2 − by an unknown NO oxidase would result in increased biomass production by N. europaea .…”
Section: Discussionmentioning
confidence: 99%
“…While production of N oxides by N. europaea has been well studied both through experimentation and modeling (4, 18, 22, 37, 38), production of N oxides by N. winogradskyi is more cryptic. Early studies reported both production of NO and N 2 O and consumption of NO by strains of N. winogradskyi and Nitrobacter vulgaris (40, 41), but only NO consumption, not production, was shown in one later study on N. winogradskyi (42).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, it was commonly accepted that hydroxylamine is oxidized to NO − 2 by hydroxylamine dehydrogenase (previously referred to as hydroxylamine oxidoreductase) in AOB (Arp & Stein, 2003). Caranto, Vilbert, and Lancaster (2016) suggested that under aerobic conditions, NO could be rapidly oxidized to NO − 2 by NO − 2 reductase, encoded by nirK, as this enzyme can act reversibly. This mechanism failed to explain fully a number of experimental observations and is now challenged by enzymatic studies that suggest that the direct product of the hydroxylamine dehydrogenase reaction is not NO − 2 but nitric oxide (NO; Caranto & Lancaster, 2017).…”
Section: Hydroxylamine Oxidationmentioning
confidence: 99%
“…In agreement with these data from pure culture studies, mesocosm experiments revealed an increased N 2 O yield in fertilized soil when ammonia oxidation was dominated by AOB (Hink et al 2018). In AOB, enzymatic N 2 O production is catalyzed by nitric oxide reductases (NOR) that convert NO derived from nitrite reduction (Kozlowski et al 2016a), and cytochrome P460, a periplasmic metalloenzyme shown to directly convert NH 2 OH to N 2 O under anaerobic conditions (Caranto et al 2016). Similar to AOA, the lack of NOR homologs in complete nitrifiers indicates that Nitrospira do not produce N 2 O via nitrifier denitrification.…”
Section: Potential Niche-defining Differences Between Strict Ammoniamentioning
confidence: 99%